THE ROLE OF FORENSIC PSYCHOLOGICAL EXAMINATION IN CRIMINAL PROCESS AND THE ALGORITHM OF PSYCHODIAGNOSTIC RESEARCH JUVENILE VICTIMS VIOLENCE - Kozlova, Anna (PSYCHOLOGICAL JOURNAL, 2017)
Forensic psychological examination is a special research and assessment of phenomena the legal reality by specialist in psychology. This special psychological research conducted in unpsychological area – the practice of law enforcement or judicial authorities. Criminal legal significance forensic psychological examination is individualizing punishment and the correct qualification of the crime according to the damage which the victim came into assault. Trauma of juvenile victims of violent assault can be not only obvious (physical), but not obvious (psychological). Forensic psychological examination has an important place in the pre-trial investigation and court proceedings as evidence, but despite certain statutory rules, the use of psychological knowledge in the investigation of crimes related to violence against juvenile, officials of the preliminary investigation and judges often do not differentiate forensic psychological and complex psychological-psychiatric examination. They thinking that psychological-psychiatric examination relate to medicine, and therefore have an advantage against the psychological examination and more reliable results. When the victim is directed to the psychological-psychiatric examination by the preliminary investigation and the court, not previously analyzed the health status of the child, it is defined as a mentally ill person that violates the rights, honor and dignity. Hence, forensic psychological examination is the processual action, which is in researching of human mental activity that does not extend beyond the norm, and conducted on behalf of the pre-trial investigation or the court, or initiated lawyer. Common subject of forensic psychological examination of mental activity a person legally significant situations within particular case. In the context of our research themes the object of this type of examination is the mental state of the juvenile victims of violent attacks, especially its cognitive processes, social intelligence, emotional and volitional, individual psychological and personality traits, and the subject – the ability to understand the nature and importance of criminal assault and provide them conscious resistance Forensic psychological examination of juvenile victims of violence – a special kind of expertise that requires expert psychologist fundamental knowledge not only the basics of psychodiagnostics, but also developmental psychology; ability to carefully examine materials of the criminal proceedings and by analyzing the right to develop his research according to character of crimes and the age of the child.